Preliminary finite element analysis of the stainless-steel liner of the maintainable test cell concept of IFMIF-DONES. (June 2022) - Katona, I.; Tóth, M.; Castellanos, J.; Arbeiter, F.; Dézsi, T.; Zsákai, A.; Micciche, G.; Qiu, Y.; Siwek, M.; Alonso, D.; Melendez, C.; Rueda, F.; et al.
Highlights: New maintainable design concept in fusion related facility. Preliminary mechanical finite element analysis of an unusual shaped vacuum vessel. Pareto front tradespace study for stiffening structure optimal variants. Abstract: The main purpose of IFMIF-DONES facility is to provide a neutron source for irradiating small specimens and producing experimental data of material properties for the construction of DEMO fusion power plant. The Test Cell (TC) of the DONES is a confined and well-shielded room, where the strong irradiation environment is created. The biological shielding of the TC mainly consists of several meters thick concrete walls and shielding plugs, and a stainless-steel liner. The TC liner and the concrete walls are actively cooled by water because of the high volumetric heating coming from nuclear reactions. Although, the TC is designed to be fully functional for the complete life span of the facility, still there is a very low probability of defect of the TC biological shielding due to their exposure of intense neutron and gamma irradiation. Therefore, the original TC configuration, which was a monolithic approach, had to be revised. Due to this reason, at the end of 2019 the project team has changed the TC concept from the monolithic design to the so-called Maintainable TC Concept (MTCC) design, which allows a maintenance possibility in case of unexpected damage.